Состав почвенного покрова и содержание гумуса в почвах территории Криворожского ботанического сада НАН Украины - Сметана, Н.Г.; Савосько, В.Н. (Промышленная ботаника, 2004)
The composition of soil cover and humus content in soils of Krivoi Rog Botanical Garden were studied. Within the pale of explored territories, the presence of two locality types was revealed: plain watershed locality and ravine one. The soil of the Garden is represented by two kinds (ordinary chernozyom and meadow-black soil) types and by four genera: carbonaceous, alluvial, washed-off, degraded. The humus content in explored soils is within the limits of 3,7 – 6,2% (for humus horizon) and 1,9 – 4,6% (for humus transitional horizon). The humus supplies of one metre soil layer put together 280-740 tons per ha.